EVALUASI PROGRAM PENJANGKAUAN PPKS OLEH SATGAS P3S DINAS SOSIAL PROVINSI DKI JAKARTA - Oktavian, Dahrul; Lebang Pakan, Marcelina Sanda (Jurnal Insani, 2025)
The group categorized as Social Welfare Service Recipients (PPKS) represents communities that experience social vulnerability and therefore require state intervention to enhance their social functioning. In response, the DKI Jakarta Provincial Government initiated the Social Services, Supervision, and Control Task Force (Satgas P3S) as the main implementing body for outreach and intervention programs. This study aims to analyze the contextual relevance and effectiveness of the PPKS outreach initiative conducted by Satgas P3S, as well as to identify its supporting elements, challenges, and resulting impacts. The study applied a qualitative descriptive method, utilizing data obtained from observations, structured interviews, and documentation analysis. Research participants consisted of Satgas P3S members, officers from the Civil Service Police Unit (Satpol PP), and managers of Social Welfare Institutions (LKS). Data interpretation followed the Miles and Huberman analytical framework, with reliability ensured through method and source triangulation. Results indicate that the outreach initiative provides substantial strategic and operational value but is still constrained by resource limitations, low community engagement, and weak interagency coordination. Through the application of the CIPP evaluation framework, it was found that the program corresponds well with Jakarta’s social context, is supported by adequate input resources, is implemented under established operational standards, and produces meaningful outcomes. In summary, the program contributes positively to mitigating social vulnerability within Jakarta. Nonetheless, further progress requires strengthened cross-sectoral partnerships, improvement of staff competence, and increased public participation.